The Biology of Monoclonal Antibodies: Focus on Calcitonin Gene-Related Peptide for Prophylactic Migraine Therapy - Raffaelli, Bianca; Reuter, Uwe (Neurotherapeutics, 2018)
Calcitonin gene-related peptide (CGRP) is 37-amino-acid neuropeptide, crucially involved in migraine pathophysiology. Four monoclonal antibodies (mAbs) targeting the CGRP pathway are currently under evaluation for the prevention of episodic and chronic migraine: eptinezumab (ALD403), fremanezumab (TEV-48125), galcanezumab (LY2951742), and erenumab (AMG334). As reviewed in this article, all 4 antibodies have been proven effective, tolerable, and safe as migraine prophylactic treatments in phase II clinical trials. The mean decrease in migraine days per month was between 3.4 and 6.3 days/month after 8 to 12 weeks of treatment, and the placebo subtracted benefit ranged from 1 to 2.18 days. Notably, up to 32% of subjects experienced total migraine freedom after drug administration. Substance class-specific adverse events and treatment-related serious adverse event did not occur. Further long-term and large-scale trials are currently under way to verify the safety and efficacy profile of mAbs. In particular, the potential risk of vascular adverse events and the role of anti-drug antibodies deserve special attention. Anti-CGRP peptide and anti-CGRP receptor antibodies are the first effective treatments, which were specifically developed for the prevention of migraine. Their site of action in migraine prevention is most likely peripheral due to large molecule size, which prevents the penetration through the blood–brain barrier and thereby shows that peripheral components play a pivotal role in the pathophysiology of a CNS disease.